The Role of Optical Coherence Tomography in the Diagnosis of Angle Closed Diseases of the Anterior Chamber. Part 1: Visualization of the Anterior Segment of the Eye - N. I. Kurysheva; G. A. Sharova (Oftalʹmologiâ, 2021)
The purpose of this work is to review the literature data on the role of optical coherence tomography in the diagnosis of diseases of the closed angle of the anterior chamber. An analysis of the modern technical devices use — optical coherence tomography of the anterior segment (AS-OST) and models with a frequency-modulated source (Swept Source) is presented. The advent of new imaging technologies such as SS-OCT is advancing the understanding of the pathogenesis of primary angle closure diseases. Visualization of the structures of the anterior segment of the eye is an important part of the strategy aimed at solving the problem of identifying risk factors, diagnosing, monitoring and evaluating the effectiveness of treatment of diseases of primary angle closure. Qualitative and quantitative data analysis based on optical coherence tomography significantly increases the diagnostic accuracy, which undoubtedly plays a key role in the choice of treatment tactics for the closed angle of the anterior chamber. The interpretation of research results should take into account the strengths and weaknesses of traditional methods and newly developed technologies.Conclusion. Optical coherence tomography of the eye’s anterior segment is a standard in modern diagnostics and evaluation of the effectiveness of treatment of diseases of primary angle closure, taking into account pathogenetic mechanisms.